An examination of Marriott's entry into the Chinese hospitality industry: A Brand Equity perspective. (June 2015) - Wong, Tommy; Wickham, Mark
Abstract: Since the Open-Door Reforms and the "opening" of the Chinese market to foreign firms in the late 1970s, numerous Western firms have sought to enter and establish their presence as a market leader in their particular industry. Recently, there has been a call to develop a finer-grained understanding of the specific organisational factors required for international hotels attempting to leverage their brand(s) into China. This paper presents an analysis of Marriott's entry into the Chinese hospitality market, with a particular interest in the resources and capabilities that the company used to effectively manage their Brand Equity in that context. This paper presents an extended Brand Equity model that incorporates the six antecedent resources categories (financial capital, internal relationships, internal operating systems and programs, international brand reputation, human capital and domestic stakeholder relationships management) and five antecedent capabilities associated with the strategic management of Marriott's Brand Equity in the Chinese hospitality market. Highlights: We present an analysis of Marriott Hotels' entry into the China. We present an extended Brand Equity model. We present 6 resources and 5 capabilities associated with Brand Equity. We identify the strategic management factors associated with entry into China. We present 3 main implications for Western firms wishing to enter into China.